[(3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio)acetamides with the fragments of carcase amines - effective SARS Coronavirus inhibitors - Berest, G. G.; Берест, Галина Григорівна (RS Global Sp. z. O.O., Scientific Educational Center, Warsaw, Poland, 2018)
It was shown, that N-cycloalkyl-(cycloalkaryl)-2-[(3-R-2-oxo-2-H-[1,2,4]triazino-[2,3-c]quinazolin-6-yl)thio]acetamides revealed antiviral activity against SARS Coronavirus in visual test for V(inhibition of viral cytopathic effect) and NR (increase in NR dye uptake). Results for each tested compound were reported as virus-inhibitory concentration, 50 % endpoint, or 90% effective concentration and cell-inhibitory concentration, 50% endpoint were determined. The high inhibiting activity of compounds was estimated. It was noted, that antiviral effect of compound 1.4 was comparable with test drug. It was shown, that planar [1,2,4]triazino[2,3-c]quinazoline system caused antiviral activity, additionally established by carcase amines fragment and depend on the nature of substituent in 3rd position.
Keywords: [(3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]]acetamides; carcase amines; SARS Coronavirus; antiviral activity; virus-inhibitory concentration; cell-inhibitory concentration